Sequência didática para ensino de microgravidade com utilização de um aparato experimental - Silva, Valgnésio Batista da (Universidade Federal Rural do Semi-Árido, 2019)
Space Physics has developed a lot in the last decades promoting a race for the exploration of the sidereal space. Thus, bringing into the school the discussion on topics related to this field of science is something necessary. In this way, the didactic sequence presented here aims to develop a discussion around the theme Microgravity with the aid of an experimental apparatus that simulates the free fall allowing students to experience meaningful learning. This work was developed in four moments, the last being the accomplishment of some experiments already cited in the specialized literature to demonstrate the effects of microgravity. The didactic sequence will address some of the physical concepts inherent in its understanding as Universal Gravitation. The experimental apparatus is easy to construct and accessible to the teacher. This aids in the development of the didactic sequence presented here, providing quite satisfactory results regarding the participation and learning of the students
Keywords: Física espacial; Microgravidade; Aprendizagem significativa; Gravitação universal; Space physics; Microgravity; Meaningful learning; Universal gravitation; CIENCIAS EXATAS E DA TERRA::FISICA